Does Digital Proficiency Actually Improve Cognitive Achievement in Bloom’s Digital Taxonomy? - Kandaga, Thesa; Kridnadi, Elang; Novianti, Idha; Nurhayati, Suci; Gusti, Valeria Yekti Kwasaning (Journal of Posthumanism, 2025)
This research explores the disparity between students’ digital proficiency and their cognitive performance within the framework of Bloom’s Digital Taxonomy (BDT) in secondary school mathematics education. The study investigates how digital skills impact students’ ability to attain cognitive outcomes across different BDT levels. Employing a qualitative case study design, it examines 127 students from four secondary schools in three major cities in Indonesia. Data were collected through cognitive tests and digital literacy assessments, covering six dimensions: information, communication, content creation, safety, problem-solving, and competence. The results indicate that while students with strong digital skills perform well in lower-order cognitive tasks (remembering, understanding, applying), they face difficulties in achieving higher-order thinking skills (analyzing, evaluating, creating). This discrepancy highlights the necessity of aligning digital engagement with cognitive development goals, ensuring that technology fosters critical thinking and creativity rather than merely supporting superficial knowledge acquisition.